Effect of agomelatine treatment on C-reactive protein levels in patients with major depressive disorder: an exploratory study in "real-world, " everyday clinical practice. (5th October 2016) - De Berardis, Domenico; Fornaro, Michele; Orsolini, Laura; Iasevoli, Felice; Tomasetti, Carmine; de Bartolomeis, Andrea; Serroni, Nicola; De Lauretis, Ida; Girinelli, Gabriella; Mazza, Monica; Valchera, Alessandro; Carano, Alessandro; et al.
Abstract : Objective: Agomelatine is a newer antidepressant but, to date, no studies have been carried out investigating its effects on C-reactive protein (CRP) levels in major depressive disorder (MDD) before and after treatment. The present study aimed (i) to investigate the effects of agomelatine treatment on CRP levels in a sample of patients with MDD and (ii) to investigate if CRP variations were correlated with clinical improvement in such patients. Methods: 30 adult outpatients (12 males, 18 females) with a Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision (DSM-IV-TR) diagnosis of MDD were recruited in "real-world, " everyday clinical practice and treated with a flexible dose of agomelatine for 12 weeks. The Hamilton Rating Scale for Depression (HAM-D) and the Snaith-Hamilton Pleasure Scale (SHAPS) were used to evaluate depressive symptoms and anhedonia, respectively. Moreover, serum CRP was measured at baseline and after 12 weeks of treatment. Results: Agomelatine was effective in the treatment of MDD, with a significant reduction in HAM-D and SHAPS scores from baseline to endpoint. CRP levels were reduced in the whole sample, with remitters showing a significant difference in CRP levels after 12 weeks of agomelatine. A multivariate stepwise linear regression analysis showed that higher CRP level variation was associated with higher baseline HAM-D scores, controlling for age, gender, smoking, BMI, and agomelatine dose. Conclusions: Agomelatine's antidepressant properties were associated with a reduction in circulating CRP levels in MDD patients who achieved remission after 12 weeks of treatment. Moreover, more prominent CRP level variation was associated with more severe depressive symptoms at baseline.